Электромагнитные процессы в симметричных индукционных системах с идентичными ферромагнитными тонкостенными экраном и листовой заготовкой - Батыгин, Ю.В.; Гнатов, А.В.; Аргун, Щ.В.; Еремина, Е.Ф. (Електротехніка і електромеханіка, 2012)
The article investigates a symmetric inductor induction system
with identical ferromagnetic thin-walled screen and sheet blank.
The basic analytical dependences for calculation of the basic
electrodynamics characteristics, namely, components of the
electromagnetic field excited in the ferromagnetic metal screen
and the sheet blank are obtained for the symmetric inductor
induction system.